SOSIALISASI PEMANFAATAN ARANG SEKAM PADI PADA MEDIA TANAM UNTUK MENDUKUNG PERTUMBUHAN BIBIT KAKAO - Ida Nursanti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Ultisol soil has poor physical and chemical soil characteristics in supporting plant growth. So that ultisol soil can be optimized for its use as a medium for planting cocoa seeds, rice husk charcoal can be used. Rice husk charcoal can increase the availability of nutrients in the soil, can store nutrients in the soil so that they are not easily leached by water and are very easily released when needed or taken up by plants. The aim of this outreach is to utilize rice husk charcoal to support the growth of cocoa plants on ultisol soil, and to promote the procurement of cocoa seeds, especially in Solok Village. The results of previous research show that applying various doses of rice husk charcoal to ultisol soil increases the soil pH, the soil structure becomes loose, hollow, the soil becomes moist and contains water. Apart from that, it also affects the growth of cocoa seedlings.